Resident opinions towards impacts of Cultural Heritage Tourism: A case of Kullu Valley, Himachal Pradesh (India) - Bansal , S.P; Thakur, Rohit; Sharma , Suman (Turizam, 2024)
Residents opinions are important for planning and sustainable cultural heritage tourism development at a destination. In the present study, data was collected through a structured questionnaire to know the opinions of local residents towards the socio-cultural and economic impacts of Cultural heritage tourism in Kullu valley. The results of the study highlight that local residents perceive cultural heritage tourism brings socio-cultural & economic benefits and support tourism development. Residents are also aware about the darker side of tourism development on the local community, culture and economy. Strong partnerships between local residents and tourism authorities are required for sustainable cultural heritage tourism development.
Keywords: Cultural Heritage Tourism, Kullu valley, Residents opinions, Sustainable planning, Tourism impacts.